Síntese e caracterização de complexos de platina (II) com ligandos fosfínicos e cloroquina : estudo de suas interações com o ADN e avaliação de suas atividades citotóxicas - Villarreal Peña, Wilmer José (2013)
In this work were synthesized and characterized complexes of general formule [Pt(P)2Cl2] and [Pt(P)2(CQ)Cl]PF6 (where (P)2= triphenylphosphine (PPh3), 1,3-bis (diphenylphosphino ) propane (dppp), 1,4-bis (diphenylphosphino) butane (dppb), 1,1 '-bis (diphenylphosphino) ferrocene (dppf) and CQ = Chloroquine). The characterization of the complexes was performed by means of elemental analysis, conductivity, absorption spectroscopy in the infrared and UV-Visible regions (IR and UV-Vis), NMR 1H, 13C{1H}, 15N{1H}, 31P{1H}, 195Pt{1H}, cyclic voltammetry and differential pulse, and mass spectrometry (in the case of chloroquine complexes). Also, the interaction of the chloroquine complexes with DNA was evaluated for calculate to the magnitude of the interaction with this important macromolecule, obtaining that the complexes showed interaction constants similar and higher than those presented by CQ and CQDP, and decrease the relative viscosity of DNA. We also evaluated the cytotoxic activity of the chloroquine complexes in the cell lines MCF-7 and MDA-MB-231 (human breast tumor cell lines), DU-145 (the human prostate tumor cell line), A549 (the human lung adenocarcinoma epithelial cell line), V79-4 (the Chinese hamster lung fibroblast cell line), and the L929 (nontumor cell line from mice), showed promissory activity, mainly of the complexes 5 and 8.